Fabrication of Citric Acid/RGD Multilayers on Mg‐Zn‐Y‐Nd Alloy via Layer‐by‐Layer Self‐Assembly for Promoting Surface Biocompatibility. Issue 13 (14th June 2021) - Kou, Fang; Liu, Changsheng; Wang, Liguo; Yasin, Aqeela; Li, Jingan; Guan, Shaokang
Abstract: Magnesium (Mg) alloy, an important biodegradable material widely investigated on cardiovascular stent, is restricted for further application due to some limited functions, such as the excessively rapid degradation rate, poor hemocompatibility, and delayed re‐endothelialization. To overcome these shortcomings, surface modification with biomolecules has attracted much attention. In this study, the multifunctional coatings of citric acid (CA) and Arg‐Gly‐Asp (RGD) via layer‐by‐layer self‐assembly are immobilized onto the polydopamine (PDA) deposited surface which is passivated with hydrofluoric acid (HF) solution before. The basic characterization results suggest that PDA/(CA‐RGD)2 coating exhibits a rich‐in‐amine and hydrophilic surface. The corrosion current density of PDA/(CA‐RGD)2 exposed to simulated body fluid is reduced by 95.65% from 1.586 × 10 −4 to 6.894 × 10 −6 A cm −2 under the protection of the dense MgF2 layer and multifunctional coatings. Besides, inhibition on platelet adhesion, hemolysis rates, and fibrinogen adsorption also prove the enhanced hemocompatibility of the PDA/(CA‐RGD)2 coatings. Meanwhile, the human umbilical vein endothelial cells (HUVECs) and smooth muscle cells (SMCs) culture results jointly prove the excellent endothelialization performance of functionalized samples. In conclusion, the above mentioned results reveal that the functionalized surface of PDA/(CA‐RGD)2 displays better overall performance, indicating a preferable application for cardiovascular stents. Abstract : The multifunctional coatings of citric acid (CA) and tripeptide sequence Arg‐Gly‐Asp (RGD) via layer‐by‐layer self‐assembly are immobilized onto the polydopamine (PDA) deposited surface which was passivated with hydrofluoric acid solution. The PDA/(CA‐RGD)2 coating not only improves hemocompatibility of Mg‐Zn‐Y‐Nd alloy, but also achieves rapid endothelialization by promoting the growth of human umbilical vein endothelial cells while inhibiting that of smooth muscle cells.